LITERARY STUDY OF MUTRASANGRAHANIYA MAHAKASHAYA WITH RESPECT TO MUTRASANGRAHANIYA KARMA (AYUSHDHARA, 2016)
The tremendous craze for junk food, fast food, canned food, untimely food intake wrong sleeping habits, causes physical as well as mental hazards like Sheetmeha, Hastimeha, hypertension along with that Insomnia, Anxiety etc. have become a very common problem.The herbal option for treatment of Sheetameha, Hastimeha etc. Mutrasangrahaniya Mahakashaya from Ayurvedic text can be used as readymade guide. In this work Mutrasangrahaniya Mahakashaya from Charak Samhita is studied. Prameha is considered as one of the emerging disease in today’s era. The cardinal symptom of Prameha in Ayurveda is Atipravrutti of Mutra which resemble to the “Diabetes”.Numerous Experiments and Research projects are performed everyday to tackle this disease. So it is very much essential to learn & understand the drugs which are crucial & can act as to key drugs in such diseases. So it is very much required to study Mutrasangrahaniya Karma. The Dravyas used for Mutrasagrahaniya Karma are mainly Kashaya rasatmaka which control the Atipravrutti of Mutra by absorbing Jaliyansh.Mutrasangrahana Karma can be defined as the activity that reduced the amount of Mutra thus restoring the normally of Ambu. Jambu, Amra, Plaksa, Udumbara, Ashvattha, Bhallataka, Vata, Asmantaka, Kapitana, Somvalka are ten herbs of Mutrasangrahaniya Mahakashaya and their Karmukatva as mentioned mainly in Charaka Samhita and if necessary, other ancient texts. These ten Dravyas mainly have Kashaya rasa, Sheeta virya, Ruksha guna and are Kapha pitta shamaka. They help in rectifying Atipravrutti of Mutra by directly and indirectly.